2017
DOI: 10.1038/srep40609
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in neuroendocrine carcinoma: biological markers are more useful than histomorphological markers

Abstract: Gastroenteropancreatic neuroendocrine carcinomas (GEP-NEC) are a very aggressive type of cancer, for which prognostic factors are lacking. We analysed clinical and histomorphological prognostic markers of overall survival (OS), completed with a record of biological and haematological data of patients diagnosed between December 2002 and December 2015. The median OS was 16 months (95% CI 13.9–18.1). After univariate analysis, performance status (PS) ≥ 2 and stage IV were associated with a worse outcome (9 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
(43 reference statements)
2
26
0
1
Order By: Relevance
“…Some authors have reported that LDH and AST are independent factors representing poor prognosis in NEC [14][15][16]. Similarly, LDH was one of the impactful prognostic factors identi ed in this study.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Some authors have reported that LDH and AST are independent factors representing poor prognosis in NEC [14][15][16]. Similarly, LDH was one of the impactful prognostic factors identi ed in this study.…”
Section: Discussionsupporting
confidence: 71%
“…However, AST was not a signi cant prognostic factor in this study. A previous study suggested a cut-off value of AST as 2 times the ULN [15], but there was only one patient with more than 2 times the ULN in this study. Therefore, to determine the prognostic signi cance of AST, a large number of patients with high AST levels should be included.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The forced expression of CHMP3 suppressed EMT program and MAPK signaling, suggesting that CHMP3 gene played an anticancer role in TNBC. Although, in human lung cancer and prostate cancer, CHMP3 gene has been reported to be expressed at a higher level, and its expression is associated with increased neuroendocrine differentiation of cancer cells (Walker, Antoniono, Ross, Paisley, & Oh, ; Wilson, Oh, Hwa, & Rosenfeld, ), which may predict poor prognosis (Chan et al, ; Freis et al, ; Terry & Beltran, ). 25.1 protein encoded by CHMP3 gene was found upregulated in M12 prostate cancer cells and non‐small‐cell lung cancer with neuroendocrine differentiation (Walker et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with GEP-NEN with a Ki67-index > 20% diagnosed between the 1st of January 2012 and 31st of December 2016 and referred to the ENETS Neuroendocrine Tumour Centre of Excellence, Rigshospitalet were included. Patients with neuroendocrine cancer of unknown primary (CUP) predominantly with abdominal metastases were also included, in agreement with several prior publications [6,10,[15][16][17][18][19][20].…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 92%